And Bardot … became a blonde: hair, stardom and modernity in post-war France. Issue 1 (2nd January 2016) - Vincendeau, Ginette
Abstract : A pretty brown-haired starlet from 1952 to 1956, Brigitte Bardot emerged as a global star and sex symbol with hair newly bleached in Roger Vadim's Et Dieu … créa la femme / And God Created Woman (1956). This article focuses on the importance of blondness to Bardot's stardom in post-war France, and how its modernity affected her cultural standing and national identity as well as the aesthetics of her films. After a close look at the significance of Bardot's hair in Et Dieu … créa la femme, the article examines the wider context of post-war France in terms of changes in both hair fashions and stardom. It then moves on to explore the implications of her striking, voluminous hairstyles, and how these functioned as a 'signature' both in and out of her films. The article argues that Bardot's blond hair was the emblem of both her modernity and her successful amalgamation of 'Franco-American stardom'.